Features that best define the heterogeneity and homogeneity of autism in preschool‐age children: A multisite case–control analysis replicated across two independent samples. Issue 3 (29th December 2021) - Wiggins, Lisa D.; Tian, Lin H.; Rubenstein, Eric; Schieve, Laura; Daniels, Julie; Pazol, Karen; DiGuiseppi, Carolyn; Barger, Brian; Moody, Eric; Rosenberg, Steven; Bradley, Chyrise; Hsu, Melanie; et al.
Abstract: The heterogeneous nature of children with symptoms of autism spectrum disorder (ASD) makes it difficult to identify risk factors and effective treatment options. We sought to identify behavioral and developmental features that best define the heterogeneity and homogeneity in 2–5‐year‐old children classified with ASD and subthreshold ASD characteristics. Children were enrolled in a multisite case–control study of ASD. Detailed behavioral and developmental data were gathered by maternal telephone interview, parent‐administered questionnaires, child cognitive evaluation, and ASD diagnostic measures. Participants with a positive ASD screen score or prior ASD diagnosis were referred for comprehensive evaluation. Children in the ASD group met study criteria based on this evaluation; children who did not meet study criteria were categorized as having subthreshold ASD characteristics. There were 1480 children classified as ASD (81.6% boys) and 594 children classified as having subthreshold ASD characteristics (70.2% boys) in the sample. Factors associated with dysregulation (e.g., aggression, anxiety/depression, sleep problems) followed by developmental abilities (e.g., expressive and receptive language skills) most contributed to heterogeneity in both groups of children. Atypical sensory response contributed to homogeneity in children classified as ASD but not those with subthreshold characteristics. These findings suggest that dysregulation and developmental abilities are clinical features that can impact functioning in children with ASD and other DD, and that documenting these features in pediatric records may help meet the needs of the individual child. Sensory dysfunction could be considered a core feature of ASD and thus used to inform more targeted screening, evaluation, treatment, and research efforts. Lay summary: The diverse nature of autism spectrum disorder (ASD) makes it difficult to find risk factors and treatment options. We identified the most dissimilar and most similar symptom(s) in children classified as ASD and as having subthreshold ASD characteristics. Factors associated with dysregulation and developmental abilities contributed to diversity in both groups of children. Sensory dysfunction was the most common symptom in children with ASD but not those with subthreshold characteristics. Findings can inform clinical practice and research.